Composition and metabolic potential of microbiomes associated with mesopelagic animals from Monterey Canyon - Corinna Breusing; Karen J. Osborn; Peter R. Girguis; Aspen T. Reese (ISME Communications, 2022)
Abstract There is growing recognition that microbiomes play substantial roles in animal eco-physiology and evolution. To date, microbiome research has largely focused on terrestrial animals, with far fewer studies on aquatic organisms, especially pelagic marine species. Pelagic animals are critical for nutrient cycling, yet are also subject to nutrient limitation and might thus rely strongly on microbiome digestive functions to meet their nutritional requirements. To better understand the composition and metabolic potential of midwater host-associated microbiomes, we applied amplicon and shotgun metagenomic sequencing to eleven mesopelagic animal species. Our analyses reveal that mesopelagic animal microbiomes are typically composed of bacterial taxa from the phyla Proteobacteria, Firmicutes, Bacteroidota and, in some cases, Campylobacterota. Overall, compositional and functional microbiome variation appeared to be primarily governed by host taxon and depth and, to a lesser extent, trophic level and diel vertical migratory behavior, though the impact of host specificity seemed to differ between migrating and non-migrating species. Vertical migrators generally showed lower intra-specific microbiome diversity (i.e., higher host specificity) than their non-migrating counterparts. These patterns were not linked to host phylogeny but may reflect differences in feeding behaviors, microbial transmission mode, environmental adaptations and other ecological traits among groups. The results presented here further our understanding of the factors shaping mesopelagic animal microbiomes and also provide some novel, genetically informed insights into their diets.